Prevalence of dental caries on individual permanent tooth in patients visiting a tertiary care center - KC, Neela; Maharjan, Anjana; Thapa, Sujan; Prasad Sharma, Bishnu (Journal of Gandaki Medical College-Nepal, 2024)
Introduction: Dental caries is considered a major public health problem globally due to its high prevalence and significant social impact. In a developing country like Nepal, the prevalence of dental caries is increasing mainly due to a lack of awareness about dental caries. Hence, the present study was designed to assess the prevalence of dental caries on individual permanent tooth surfaces. Methods: This cross-sectional study was conducted in 384 patients visiting Patan Hospital, aged above 18 years where a convenience sampling technique was used for data collection. After the diagnosis of dental caries was made, each surface of caries was recorded on the proforma sheet for both maxillary and mandibular teeth. This sheet included mesial, distal, lingual/palatal, buccal/labial, incisal/occlusal surfaces. Results: A total of 1194 carious surfaces were recorded in 384 participants. Caries distribution was higher in maxillary arch 614(51.40%) than in mandible 580(48.60%). The majority of caries affected teeth were first molars followed by second molars. Conclusions: In this study, the prevalence of caries was higher in the maxillary arch than in the mandibular arch and the most affected tooth was the mandibular first molar and the least was mandibular central incisors. Similarly, more females were affected than males, and a higher proportion of caries were found in the age group between 18 to 35 years.